2019
DOI: 10.3390/molecules24193558
|View full text |Cite
|
Sign up to set email alerts
|

General Synthesis of 1-Aryl-6-azaisocytosines and Their Utilization for the Preparation of Related Condensed 1,2,4-Triazines

Abstract: A simple general synthesis of 1-aryl-6-azaisocytosine-5-carbonitriles 4 is described. This method is based on coupling diazonium salts with cyanoacetylcyanamide 2 and then cyclization of the formed 2-arylhydrazono-2-cyanoacetylcyanamides 3. The 6-azaisocytosines 4 were studied with respect to tautomeric equilibrium and the transformation of functional groups, and used in the synthesis of the condensed heterocyclic compounds: Purine isosteric imidazo[2,1-c]-[1,2,4]triazine 8 and the 1,2,4-triazino[2,3-a]quinazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Fused azaisocytosine-containing congeners with the acetohydrazide functional group (1-4, Figure 1), which is prone to quick oxidation, are an important class of nitrogen-rich heterocycles. All these annelated triazinylacetic acid hydrazides, including the parent compound (1, as an unsubstituted structure) and the remaining para-substituted derivatives (2)(3)(4), have been synthesised formerly, and their spectroscopic data were consistent with the assigned structures shown in Figure 1 [1]. These compounds have previously been subjected to extensive biological assays evaluating their reducing power and antioxidant potential, as a result of which some of them have been disclosed as new, promising antioxidant agents with prospective utility in the treatment of diseases induced by reactive oxygen species and non-radical reactive oxygen metabolites.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fused azaisocytosine-containing congeners with the acetohydrazide functional group (1-4, Figure 1), which is prone to quick oxidation, are an important class of nitrogen-rich heterocycles. All these annelated triazinylacetic acid hydrazides, including the parent compound (1, as an unsubstituted structure) and the remaining para-substituted derivatives (2)(3)(4), have been synthesised formerly, and their spectroscopic data were consistent with the assigned structures shown in Figure 1 [1]. These compounds have previously been subjected to extensive biological assays evaluating their reducing power and antioxidant potential, as a result of which some of them have been disclosed as new, promising antioxidant agents with prospective utility in the treatment of diseases induced by reactive oxygen species and non-radical reactive oxygen metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the strongest scavenger of hydrogen peroxide proved to be the ethoxy derivative (4), whose effect is better than that of standard antioxidants. For all the molecules bearing the common acetohydrazide pharmacophore (1)(2)(3)(4), the mechanism of their antiradical action (through hydrogen atom transfer to the DPPH  ) has already been established [1]. This makes them promising drug candidates in the preclinical phase of drug development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were designed as functionalised isosteric isomers of azacytosine. Having the amino nitrogen locked up in an imidazolidine ring, these innovative small molecules may be of biochemical interest as they are suspected to be resistant to enzymatic deamination, unlike short-acting cytosine-or azacytosine-based drugs (such as cytarabine, gemcitabine, or azacytidine, respectively), which are susceptible to inactivation by cytidine deaminase [7][8][9]. Therefore, their development may contribute to the discovery of more effective and metabolically stable azaisocytosine-based drugs for anticancer chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…A number of bioorganic compounds containing a core structural component of asymmetrical triazine, i.e., 1,2,4-triazine, found utility as molecular pharmaceutics [ 6 , 7 ]. Nevertheless, a literature search revealed that there were only a few scientific reports on the thermal analysis of medicines structurally based on the 1,2,4-triazine system [ 8 , 9 ] as well as those containing the template of 2-methyl-3-sulfanyl-1,2-dihydro-1,2,4-triazine-5,6-dione linked via a methylene bridge with a cephem-based hybrid structure [ 10 ] or the 1,2,4-triazin-4(3 H )-one nucleus incorporated into the structure of diazolo-annelated triazinone [ 11 ].…”
Section: Introductionmentioning
confidence: 99%